Constitutional Law on The Discretionary of Prosecutor’s Power Against Abuse of Power Implications of Corruption Culture in The Prosecutor’s Office Republic of Indonesia - Bambang Hermanto, Asep; Slamet Riyadi, Bambang (International Journal of Criminology and Sociology, 2022)
Indonesia is a rule of law, which means that there is a guarantee for the functioning of an independent or independent prosecutor in carrying out the judiciary and other tasks and for upholding law and justice based on the state constitution and the prevailing laws and regulations. The Attorney General’s Office (AGO) is a state institution in Indonesian constitutional law that can carry out or have authority on behalf of the state in prosecution and also has other powers based on applicable provisions. The problem of this research is that the discretionary power of prosecution is too loose a tendency to abuse power to commit a criminal act. terrorized corruption culture This research is qualitative and normative juridical. The discretion that is too free for prosecutors tends to abuse power to carry out a culture of corruption in the Prosecutor’s Office (PO). Researchers suggest that discretionary power in state institutions is limited and supervised by external agencies on the performance of prosecutors so that checks and balances occur in state prosecutors’ institutions.